EVALUASI KETERWAKILAN PEREMPUAN DI PARTAI POLITIK (Studi kasus DPC Partai Gerindra Jakarta Utara) - Zakiyah, Ummi; idrus, iqbal aidar; Koonah, Koonah (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2021)
The purpose of this study was to determine the evaluation of women's representation policies in the Gerindra Party with a case study of the North Jakarta Gerindra Party DPC. The concept of this research used in this research is to use the type of qualitative research with a descriptive approach. Then the data collection technique is done by interview, observation, and documentation. Miles and Hubermen qualitative data analysis technique. The results showed that the evaluation of the policy on women's representation of the North Jakarta Gerindra Party DPC in a managerial structure had fulfilled the 30% quota for women's representation. However, in terms of women's representation in parliament, it seems that the Gerindra Party must still pay attention to women's representation because at the DKI Jakarta DPRD level there is a decline in fulfilling the 30% quota. It can be concluded that the evaluation of the Gerindra Party's women's representation policy has not been maximized in terms of the role of female cadre members at the parliamentary level.